Online viva voce as a formative assessment method in forensic medicine during COVID-19 pandemic - G N Pramod Kumar; A N Roopa Urs; Malatesh Undi; Shankar M Bakkannavar (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Conducting online classes and assessment during the COVID-19 pandemic is not without challenges. The world of medical education is adapting online training and assessment because of COVID-19 pandemic restrictions. The present study was conducted to assess the students' perception regarding the process, difficulties encountered and perceived effectiveness of online assessment. MATERIALS AND METHODS: Online viva-voce (theory and visual based) was conducted in a government medical college in Karwar, Karnataka, India using videoconferencing application (Google Meet) to 149 second MBBS students as a formative assessment in 2020 over 3 months. Ten students per day joined Google Meet, 10 questions were asked to each student and assessed using a tutor marking system (on-spot). A feedback questionnaire (Google Form) was administered to students who attended online Viva-Voce. Data was analysed using descriptive and inferential statistics (Student's t-test). RESULTS: Out of 149 students, 132 participated and responded to a feedback questionnaire. Majority of the participants (91%) agreed that questions covered all topics kept for viva, 82% of them felt it would be helpful for performance in final examinations. Thirty percent of students faced network issues at their places, 45% felt nervous while facing viva in the presence of other students and 35% of participants preferred online methods over traditional viva voce. Online viva voce can be transparent (90%) and less biased (88%) if done in structured format. CONCLUSION: Online viva-voce may become relevant and effective in medical education assessment with transparent marking system for students' performance.